Preparation method and application of epoxy resin-glass fiber cloth-melamine compound-aluminum diethylphosphinate blended epoxy resin with high flame retardance and high toughness

Through the preparation of epoxy resin-glass fiber cloth-melamine compound-diethylphosphinate blended materials, the problems of flammability and insufficient flame retardancy of traditional epoxy resin materials at high temperatures are solved, and high resistance is achieved It takes into account both ignition and high toughness and is suitable for high safety requirements.

CN119286023APending Publication Date: 2025-01-10HARBIN UNIV OF SCI & TECH
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411635054.5
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-15
Publication Date
2025-01-10

AI Technical Summary

Technical Problem

Traditional epoxy resin materials are prone to flammability in high temperature or fire environments and release harmful gases, which are not flame retardant, and the use of environmentally friendly flame retardant alone will affect the mechanical properties of the material, making it difficult to have both high flame retardancy and high toughness.

Method used

Using epoxy resin-glass fiber cloth-melamine compound-diethylphosphinate aluminum blended material, it is formed by magnetic stirring and mixing at a temperature of 90-110°C and temperature gradient curing in a vacuum oven to form a high flame retardant and high toughness composite materials.

Benefits of technology

It achieves the stability and chemical corrosion resistance of the material in high temperature and harsh environments, has excellent flame retardant properties and mechanical properties, avoids the release of harmful gases, and is suitable for use in areas with high safety requirements.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119286023A_ABST
    Figure CN119286023A_ABST
Patent Text Reader

Abstract

The invention discloses a preparation method and application of epoxy resin-glass fiber cloth-melamine compound-aluminum diethylphosphinate blended epoxy resin with high flame retardance and high toughness, and relates to the technical field of polymer composite materials. The invention aims to solve the problem that the traditional composite epoxy resin material cannot have high flame retardance and high toughness at the same time. The epoxy resin-glass fiber cloth-melamine compound-aluminum diethylphosphinate blended epoxy resin prepared by the preparation method disclosed by the invention keeps stable performance in a high-temperature and severe environment, and has good weather resistance, chemical corrosion resistance and dimensional stability. Modification is performed through an environment-friendly halogen-free flame-retardant system, and the adopted melamine compound and aluminum diethylphosphinate are both halogen-free environment-friendly flame retardants, so that release of toxic gas in the combustion process can be effectively reduced. The invention can obtain the preparation method and the application of the epoxy resin-glass fiber cloth-melamine compound-aluminum diethyl phosphinate blended epoxy resin with high flame retardance and high toughness.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of polymer composite materials, and in particular to a preparation method and application of a highly flame-retardant and highly tough epoxy resin-glass fiber cloth-melamine compound-diethylaluminum phosphinate blended epoxy resin. Background Art

[0002] Epoxy resin (EP) is widely used in the fields of construction, electronics, electrical engineering, transportation, etc. due to its excellent adhesion, heat resistance and mechanical properties. However, traditional epoxy resin materials often have the disadvantages of insufficient toughness and poor flame retardancy, especially in high temperature or fire environment, they are easy to burn and release harmful gases, thus limiting their application in fields with high safety requirements.

[0003] Flame retardant modification is currently one of the main research directions for improving the performance of epoxy resin materials. Although traditional flame retardants, such as halogen flame retardants, can effectively improve the flame retardant properties of materials, they will produce toxic and corrosive gases during combustion, which seriously harm the environment and human health, and are therefore gradually restricted in their use. In order to solve this problem, environmentally friendly halogen-free flame retardants, such as melamine compounds and aluminum diethylphosphinate, have received widespread attention. Melamine compounds can effectively prevent the spread of flames because they can form a carbonized layer and release nitrogen at high temperatures, while aluminum diethylphosphinate, as a new type of flame retardant, has excellent smoke suppression effects and synergistic flame retardant properties.

[0004] However, the use of these flame retardants alone often affects the mechanical properties of the material, such as toughness and strength, while improving the flame retardant properties of the material. In addition, epoxy resin is prone to brittle failure under high stress conditions, which limits its service life in certain applications. In order to solve the above problems, glass fiber reinforced epoxy resin has become an effective solution. Glass fiber can not only significantly improve the mechanical strength and toughness of epoxy resin, but also maintain good dimensional stability at high temperatures. However, the interfacial adhesion between glass fiber and epoxy resin still needs to be optimized. At the same time, how to further improve the flame retardant properties of the material while maintaining mechanical properties is also a key difficulty in the current technological development. Summary of the invention

[0005] The purpose of the present invention is to solve the problem that traditional composite epoxy resin materials cannot have both high flame retardancy and high toughness, and to provide a preparation method and application of a highly flame retardant and high toughness epoxy resin-glass fiber cloth-melamine compound-diethyl aluminum phosphinate blended epoxy resin.

[0006] A method for preparing a highly flame-retardant and high-toughness epoxy resin-glass fiber cloth-melamine compound-diethylphosphinate aluminum blended epoxy resin is carried out according to the following steps:

[0007] Step S1:

[0008] Adding melamine compound and / or aluminum diethylphosphinate to epoxy resin, stirring magnetically at a temperature of 90 to 110° C. under ultrasonic conditions until the mixture is uniform, adding curing agent, and continuing magnetic stirring until the mixture is uniform, to obtain an epoxy resin mixed solution; the addition amounts of aluminum diethylphosphinate and melamine compound are 8% and 7%, 9% and 6%, 10% and 5%, 15% and 0%, or 0% and 15% of the mass of the epoxy resin, respectively;

[0009] Step S2:

[0010] Pour the epoxy resin mixed solution obtained in step S1 evenly into the mold, and then immerse the cut glass fiber cloth in the epoxy resin mixed solution, and ensure that the epoxy resin mixed solution is evenly filled in the gaps between the fibers of the glass fiber cloth;

[0011] Step S3:

[0012] The film mold in step S2 is placed in a vacuum oven for temperature gradient curing. After complete curing, a highly flame-retardant and high-toughness epoxy resin-glass fiber cloth-melamine compound-diethylaluminum phosphinate blended epoxy resin is obtained.

[0013] The invention discloses an application of a highly flame-retardant and highly tough epoxy resin-glass fiber cloth-melamine compound-diethylaluminum phosphinate blended epoxy resin, and an application of the highly flame-retardant and highly tough epoxy resin-glass fiber cloth-melamine compound-diethylaluminum phosphinate blended epoxy resin in an environmentally friendly halogen-free flame-retardant material.

[0014] Principle of the present invention:

[0015] Glass fiber cloth is used as a reinforcing substrate to improve the mechanical strength and toughness of the material; epoxy resin is used as a matrix material to give the material excellent adhesion, heat resistance and chemical stability; melamine compounds are used as flame retardants, which can form a carbonized layer at high temperatures and release inert gases to prevent the spread of flames; aluminum diethylphosphinate is used as a synergistic flame retardant, which has excellent smoke suppression properties and flame retardant effects, and improves flame retardant efficiency through the synergistic effect of gas phase and condensed phase.

[0016] In the present invention, due to the introduction of glass fiber and the modification of epoxy resin, the material can maintain stable performance under high temperature and harsh environment, and at the same time exhibits strong chemical corrosion resistance, and is suitable for applications under harsh working conditions. By blending melamine compound and aluminum diethylphosphinate with epoxy resin, the composite material formed not only has excellent flame retardant properties, but also retains the excellent mechanical properties and toughness of the epoxy resin itself. This blending method optimizes the flame retardancy and toughness of the material.

[0017] Beneficial effects of the present invention:

[0018] (1) The present invention provides a method for preparing a highly flame-retardant and high-toughness epoxy resin-glass fiber cloth-melamine compound-diethylphosphinate aluminum blended epoxy resin, wherein melamine compound powder and diethylphosphinate aluminum are dissolved in epoxy resin in different mass ratios to form a mixed solution, and then the mixed solution is impregnated with glass fiber cloth and cast into a mold for drying. According to the flame retardant properties, the composite material needs to have high flame retardant strength. Pure EP itself has poor flame retardant properties, while melamine compounds and diethylphosphinate aluminum contain a large amount of flame retardant elements. P-containing flame retardants can usually act in the gas phase and condensed phase during combustion, which is due to the formation of P-derived free radicals and phosphorus / phosphates, while N and B-containing flame retardants can enhance the flame retardant efficiency by releasing inert gases or by promoting the formation of denser carbon.

[0019] (2) The epoxy resin-glass fiber cloth-melamine compound-diethylphosphinate aluminum blended epoxy resin prepared by the method of the present invention has excellent flame retardant properties and mechanical properties. The reasonable ratio of melamine compound and diethylphosphinate aluminum not only enhances the flame retardancy of epoxy resin, but also takes into account the toughness of the material, overcomes the problem of brittleness of traditional flame retardant materials, and enables the material to have better anti-fracture ability when impacted or bent. The flame retardant component used has environmental protection characteristics, does not contain halogen substances, avoids the generation of harmful gases during combustion, and meets the current requirements for environmental protection and safety of materials. The preparation method of the present invention is simple and easy to operate through conventional stirring, pouring, impregnation, drying and other steps, is suitable for large-scale production, and can ensure the stable performance of the product by controlling parameters such as temperature and time. The material not only has excellent mechanical properties, but also shows strong weather resistance, is suitable for use under various harsh environmental conditions, and has a wide range of application prospects.

[0020] (3) The epoxy resin-glass fiber cloth-melamine compound-diethylphosphinate aluminum blended epoxy resin prepared by the present invention can maintain stable performance under high temperature and harsh environment, has good weather resistance, chemical corrosion resistance and dimensional stability, and is particularly suitable for the fields of construction, electronics, electrical and transportation. At the same time, the melamine compound and diethylphosphinate aluminum used are both halogen-free and environmentally friendly flame retardants, which can effectively reduce the release of toxic gases during combustion and meet environmental protection and safety requirements.

[0021] The invention can obtain a preparation method and application of a highly flame-retardant and highly tough epoxy resin-glass fiber cloth-melamine compound-diethylaluminum phosphinate blended epoxy resin. BRIEF DESCRIPTION OF THE DRAWINGS

[0022] Figure 1The infrared spectrum of the novel melamine compound prepared in the present invention is shown, MA represents unpurified melamine, PA represents unpurified phytic acid aqueous solution, BA represents unpurified boric acid, and MPBA represents a synthesized novel melamine compound environmentally friendly flame retardant;

[0023] Figure 2 A 20 μm scanning electron microscope image showing the novel melamine compound prepared in the present invention;

[0024] Figure 3 10 μm scanning electron microscope image showing the novel melamine compound prepared in the present invention;

[0025] Figure 4 represents an XRD test pattern of the novel melamine compound prepared in the present invention, MA represents unpurified melamine, BA represents unpurified boric acid, PA represents an unpurified phytic acid aqueous solution, and MPBA represents a synthesized novel melamine compound environmentally friendly flame retardant;

[0026] Figure 5 The graphs show the limiting oxygen index test (LOI) and vertical burning test (UL-94) of the epoxy resin-glass fiber cloth-melamine compound-diethylphosphinate aluminum blended epoxy resin prepared by the present invention; EP / B represents pure epoxy resin impregnated with glass fiber cloth, EP / B / MPBA 15 It means that 15% of melamine compound is mixed into epoxy resin and glass fiber cloth is immersed in epoxy resin, EP / B / ADP 15 It means that 15% of aluminum diethylphosphinate is mixed into epoxy resin and glass fiber cloth is immersed in epoxy resin, EP / B / ADP 8 / MPBA 7 It means that 8% by mass of aluminum diethylphosphinate and 7% by mass of melamine compound are mixed into epoxy resin and glass fiber cloth is immersed in epoxy resin, EP / B / ADP 10 / MPBA 5 It means that 10% by mass of aluminum diethylphosphinate and 5% by mass of melamine compound are mixed into epoxy resin and glass fiber cloth is immersed in the epoxy resin;

[0027] Figure 6 The vertical combustion (UL-94) diagram of epoxy resin-glass fiber cloth-melamine compound-diethylphosphinate aluminum blended epoxy resin prepared by the present invention is shown in FIG. EP / B represents pure epoxy resin impregnated with glass fiber cloth, and EP / B / MPBA represents 15 It means that 15% of melamine compound is mixed into epoxy resin and glass fiber cloth is immersed in epoxy resin, EP / B / ADP 15It means that 15% of aluminum diethylphosphinate is mixed into epoxy resin and glass fiber cloth is immersed in epoxy resin, EP / B / ADP 8 / MPBA 7 It means that 8% by mass of aluminum diethylphosphinate and 7% by mass of melamine compound are mixed into epoxy resin and glass fiber cloth is immersed in epoxy resin, EP / B / ADP 10 / MPBA 5 It means that 10% by mass of aluminum diethylphosphinate and 5% by mass of melamine compound are mixed into epoxy resin and glass fiber cloth is immersed in the epoxy resin;

[0028] Figure 7 The tensile test diagram of the epoxy resin-glass fiber cloth-melamine compound-diethylphosphinate aluminum blended epoxy resin prepared by the present invention is shown in FIG. EP / B represents pure epoxy resin impregnated with glass fiber cloth, and EP / B / MPBA represents 15 It means that 15% of melamine compound is mixed into epoxy resin and glass fiber cloth is immersed in epoxy resin, EP / B / ADP 15 It means that 15% of aluminum diethylphosphinate is mixed into epoxy resin and glass fiber cloth is immersed in epoxy resin, EP / B / ADP 8 / MPBA 7 It means that 8% by mass of aluminum diethylphosphinate and 7% by mass of melamine compound are mixed into epoxy resin and glass fiber cloth is immersed in epoxy resin, EP / B / ADP 10 / MPBA 5 It means that 10% by mass of aluminum diethylphosphinate and 5% by mass of melamine compound are mixed into epoxy resin and glass fiber cloth is immersed in the epoxy resin;

[0029] Figure 8 The bending test diagram of the epoxy resin-glass fiber cloth-melamine compound-diethylphosphinate aluminum blended epoxy resin prepared by the present invention is shown in FIG. EP / B represents pure epoxy resin impregnated with glass fiber cloth, and EP / B / MPBA represents 15 It means that 15% of melamine compound is mixed into epoxy resin and glass fiber cloth is immersed in epoxy resin, EP / B / ADP 15 It means that 15% of aluminum diethylphosphinate is mixed into epoxy resin and glass fiber cloth is immersed in epoxy resin, EP / B / ADP 8 / MPBA 7 It means that 8% by mass of aluminum diethylphosphinate and 7% by mass of melamine compound are mixed into epoxy resin and glass fiber cloth is immersed in epoxy resin, EP / B / ADP10 / MPBA 5 It means that 10% by mass of aluminum diethylphosphinate and 5% by mass of melamine compound are mixed into epoxy resin and glass fiber cloth is immersed in the epoxy resin.

[0030] Note: Figure 5-Figure 8 The mass fractions of melamine compound and aluminum diethylphosphinate are expressed as a percentage of the mass of epoxy resin. DETAILED DESCRIPTION

[0031] Specific implementation method 1: In this implementation method, a method for preparing a highly flame-retardant and high-toughness epoxy resin-glass fiber cloth-melamine compound-diethylphosphinate aluminum blended epoxy resin is carried out according to the following steps:

[0032] Step S1:

[0033] Adding melamine compound and / or aluminum diethylphosphinate to epoxy resin, stirring magnetically at a temperature of 90 to 110° C. under ultrasonic conditions until the mixture is uniform, adding curing agent, and continuing magnetic stirring until the mixture is uniform, to obtain an epoxy resin mixed solution; the addition amounts of aluminum diethylphosphinate and melamine compound are 8% and 7%, 9% and 6%, 10% and 5%, 15% and 0%, or 0% and 15% of the mass of the epoxy resin, respectively;

[0034] Step S2:

[0035] Pour the epoxy resin mixed solution obtained in step S1 evenly into the mold, and then immerse the cut glass fiber cloth in the epoxy resin mixed solution, and ensure that the epoxy resin mixed solution is evenly filled in the gaps between the fibers of the glass fiber cloth;

[0036] Step S3:

[0037] The film mold in step S2 is placed in a vacuum oven for temperature gradient curing. After complete curing, a highly flame-retardant and high-toughness epoxy resin-glass fiber cloth-melamine compound-diethylaluminum phosphinate blended epoxy resin is obtained.

[0038] Specific embodiment 2: This embodiment differs from specific embodiment 1 in that the melamine compound described in step S1 is prepared according to the following steps:

[0039] Under the condition of condensation and reflux, melamine is added into deionized water, an oil bath is heated to 80-100° C., and after stirring until the melamine is fully dissolved, a phytic acid solution at 60-70° C. is uniformly added, and then condensation reflux is stirred at 80-100° C. for 1 h to 2 h to obtain a light silver precipitate; a boric acid solution at 60-70° C. is continuously added uniformly, and condensation reflux is continuously stirred at 80-100° C. for 1 h to 2 h to obtain a flocculent precipitate; the flocculent precipitate is filtered, and then washed with deionized water three times and dried to obtain a melamine compound.

[0040] The other steps are the same as those in the first specific implementation.

[0041] Specific implementation method three: This implementation method is different from specific implementation methods one or two in that: the product is first washed in deionized water at 50-60°C, then placed in a vacuum oven for drying, and then the above operation is repeated twice, and finally dried at 70-80°C overnight to obtain a melamine compound.

[0042] The other steps are the same as those in the first or second embodiment.

[0043] Specific embodiment 4: The difference between this embodiment and specific embodiments 1 to 3 is that the ratio of the mass of melamine to the volume of deionized water is (9.2-9.6) g: (300-350) mL; the ratio of the mass of phytic acid in the phytic acid solution to the volume of deionized water is (11.6-12.1) g: (30-35) mL; the ratio of the mass of boric acid in the boric acid solution to the volume of deionized water is (1.45-1.65) g: (15-20) mL.

[0044] The other steps are the same as those in Specific Embodiments 1 to 3.

[0045] Specific implementation mode 5: The difference between this implementation mode and specific implementation modes 1 to 4 is that the ultrasonic time in step S1 is 10 to 20 minutes.

[0046] The other steps are the same as those in Specific Embodiments 1 to 4.

[0047] Specific implementation method 6: The difference between this implementation method and specific implementation methods 1 to 5 is that the time of magnetic stirring in step S1 is 2 to 4 hours, and the time of continuing magnetic stirring is 45 to 60 minutes.

[0048] The other steps are the same as those in Specific Embodiments 1 to 5.

[0049] Specific embodiment 7: The difference between this embodiment and specific embodiments 1 to 6 is that the curing agent in step S1 is diaminodiphenylmethane, and the added amount of diaminodiphenylmethane is 0.25-0.26% of the mass of the epoxy resin.

[0050] The other steps are the same as those in Specific Embodiments 1 to 6.

[0051] Specific embodiment eight: The difference between this embodiment and specific embodiments one to seven is: the temperature gradient curing described in step S3: first cure at 80-100°C for 1-2h, then cure at 100-120°C for 1-2h, and then cure at 120-140°C for 1-2h.

[0052] The other steps are the same as those in Specific Embodiments 1 to 7.

[0053] Specific embodiment 9: The difference between this embodiment and specific embodiments 1 to 8 is that the added amounts of the diethyl aluminum phosphinate and the melamine compound are 8% and 7% or 10% and 5% of the mass of the epoxy resin, respectively.

[0054] The other steps are the same as those in Specific Embodiments 1 to 8.

[0055] Specific embodiment ten: This embodiment discloses an application of a highly flame retardant and high toughness epoxy resin-glass fiber cloth-melamine compound-diethylaluminum phosphinate blended epoxy resin, and the application of the highly flame retardant and high toughness epoxy resin-glass fiber cloth-melamine compound-diethylaluminum phosphinate blended epoxy resin in environmentally friendly halogen-free flame retardant materials.

[0056] The following examples are used to verify the beneficial effects of the present invention:

[0057] Example 1: A method for preparing a highly flame-retardant and highly tough epoxy resin-glass fiber cloth-melamine compound-diethylphosphinate aluminum blended epoxy resin, according to the following steps:

[0058] Step S1:

[0059] Under condensation reflux conditions, add 300 mL of deionized water and 9.45 g of melamine to a three-necked flask, heat the oil bath to 90°C, stir until the melamine is fully dissolved, dissolve 11.8 g of phytic acid in 30 mL of deionized water at 60°C, then drip into the melamine solution at a uniform rate using a constant drop funnel, and then condense and reflux at 90°C with stirring for 2 h to obtain a light silver precipitate;

[0060] Then, 1.55 g of boric acid was dissolved in 15 mL of deionized water at 60° C., and then the solution was uniformly dripped into the solution using a constant drop funnel, and the mixture was continuously condensed and refluxed at 90° C. with stirring for 2 h to obtain a flocculent precipitate; the flocculent precipitate was filtered, and then washed in deionized water at 60° C. to obtain a white filter cake, and the obtained white filter cake was placed in a culture dish, and the culture dish was placed in a vacuum oven for drying, and then the above operation was repeated twice, and finally dried at 80° C. overnight to obtain a melamine compound powder;

[0061] Add melamine compound powder and / or aluminum diethylphosphinate to epoxy resin, then add the mixture to a magnetic stirrer, perform ultrasonic treatment for 10 minutes and magnetic stirring for 2 hours at a temperature of 100° C. until the mixture is uniformly mixed, add curing agent diaminodiphenylmethane, continue magnetic stirring for 60 minutes, place the mixed epoxy resin in an ultrasonic machine to perform ultrasonic treatment to remove bubbles and make the powder more uniformly distributed, and obtain an epoxy resin mixed solution;

[0062] Step S2:

[0063] The epoxy resin mixed solution obtained in step S1 is evenly poured into the polytetrafluoroethylene film of the desired test sample, and then the cut glass fiber cloth is immersed in the epoxy resin mixed solution, and the epoxy resin mixed solution is ensured to evenly fill the gaps between the fibers of the glass fiber cloth;

[0064] Step S3:

[0065] The film mold in step S2 is placed in a vacuum oven, first cured at 100°C for 2 hours, then cured at 120°C for 2 hours, and then cured at 140°C for 1 hour. After complete curing, a highly flame-retardant and high-toughness epoxy resin-glass fiber cloth-melamine compound-diethylaluminum phosphinate blended epoxy resin is obtained, wherein the mass fraction of diethylaluminum phosphinate in the epoxy resin is 8%, and the mass fraction of melamine compound in the epoxy resin is 7%.

[0066] Example 2: In this example, the mass fraction of aluminum diethylphosphinate in the epoxy resin is 9%, and the mass fraction of melamine compound in the epoxy resin is 6%. Other experimental conditions are the same as those in Example 1.

[0067] Example 3: In this example, the mass fraction of aluminum diethylphosphinate in the epoxy resin is 10%, and the mass fraction of melamine compound in the epoxy resin is 5%. Other experimental conditions are the same as those in Example 1.

[0068] Example 4: In this example, the mass fraction of aluminum diethylphosphinate in the epoxy resin is 15%, and the mass fraction of melamine compound in the epoxy resin is 0%. Other experimental conditions are the same as those in Example 1.

[0069] Example 5: In this example, the mass fraction of aluminum diethylphosphinate in the epoxy resin is 0%, the mass fraction of melamine compound in the epoxy resin is 15%. Other experimental conditions are the same as those in Example 1.

[0070] Comparative Example 1: Preparation of epoxy resin;

[0071] Step 1: Weigh the curing agent (diaminodiphenylmethane) and the epoxy resin matrix respectively according to the mass ratio of the curing agent (diaminodiphenylmethane) to the epoxy matrix of (25-30): (85-95); preheat the epoxy resin matrix at 100° C. for 30 minutes with magnetic stirring to reduce the viscosity of the epoxy resin matrix;

[0072] Step 2: Add the curing agent to the epoxy resin matrix, and stir the mixture under magnetic stirring at 80°C for 1 hour; pour the mixed epoxy resin into the mold, immerse the glass fiber cloth in the epoxy resin, and then put the mold into a vacuum oven to dry for 5 hours;

[0073] Step 3: Take out the completely degassed composite slurry and place it in an oven for curing. The curing process is 100°C / 2 hours + 120°C / 2 hours + 140°C / 1 hour. After complete curing, an epoxy resin / glass fiber cloth composite material is obtained.

[0074] Figure 1 The infrared spectrum of the novel melamine compound prepared in the present invention is shown, MA represents unpurified melamine, PA represents unpurified phytic acid aqueous solution, BA represents unpurified boric acid, and MPBA represents a synthesized novel melamine compound environmentally friendly flame retardant; Figure 1 As shown in the FTIR spectrum of MA, 3471 and 3140 cm -1 The characteristic absorption peak at -NH 2 The stretching vibration of the group, while 1674, 1551 and 1028 cm -1 The characteristic absorption peaks at 1627 and 965 cm-1 belong to NH bending vibration, C=N vibration and CN vibration respectively. The FTIR spectrum of PA shows that P=O and PO have the peaks at 1627 and 965 cm-1 respectively. -1 In the FTIR spectrum of BA, at 3214 cm -1 The broad peaks at 1459 and 1195 cm-1 may correspond to OH stretching vibrations, which are caused by the hydroxyl groups in the boronic acid molecules. -1 The peaks at 3363 and 3112 cm-1 are probably related to the vibration of BO. These peaks are typical of boric acid. -1 There is a weak peak at the bottom, which belongs to the -NH 2 The peaks of NH, C=N and CN shifted to 1674, 1507 and 1080 cm-1 , further confirming the complexation reaction between MA, PA and BA. It is worth noting that at 1674 cm -1 The peak at is assigned to NH 3+ These results indicate that the synthesis of MBA is successful.

[0075] Figure 2 The 20 μm scanning electron microscope image of the novel melamine compound prepared in the present invention is shown. Figure 3 10 μm scanning electron microscope image showing the novel melamine compound prepared in the present invention; Figure 2-3 As shown, the synthesized new melamine compound environmentally friendly flame retardant is a micron-sized flake structure with a flake diameter of 5um to 20um and contains B, C, N, O and P elements.

[0076] Figure 4 represents the XRD test pattern of the novel melamine compound prepared in the present invention, MA represents unpurified melamine, BA represents unpurified boric acid, PA represents unpurified phytic acid aqueous solution, and MPBA represents a synthesized novel melamine compound environmentally friendly flame retardant; Figure 4 As shown, the crystal structure of MA is clearly confirmed by the peaks at 13.1nm, 17.7nm, 21.6nm, 26.1nm, 28.8nm and 29.7nm. The strong and sharp peak at 26.1nm indicates that the sample has a dominant crystal phase or a highly ordered crystal structure, and the other small peaks may indicate a minor phase or a smaller amount of crystal phase. There are significant diffraction peaks at 14.7nm, 15.0nm and 28.1nm. The sample has lower intensity and fewer peaks, indicating that its crystal structure may be different from that of MA. The sharp peak at 28.1nm shows that the sample has a more clear crystal structure, but relatively fewer phases or simpler crystal features. In contrast, multiple peaks of MPBA can be observed, indicating that it contains different crystal structures. It is worth noting that the diffraction peaks at 17.3nm, 26.0nm and 28.1nm reveal the successful formation of MPBA.

[0077] Figure 5 The graphs show the limiting oxygen index test (LOI) and vertical burning test (UL-94) of the epoxy resin-glass fiber cloth-melamine compound-diethylphosphinate aluminum blended epoxy resin prepared by the present invention; EP / B represents pure epoxy resin impregnated with glass fiber cloth, EP / B / MPBA 15 It means that 15% of melamine compound is mixed into epoxy resin and glass fiber cloth is immersed in epoxy resin, EP / B / ADP 15 It means that 15% of aluminum diethylphosphinate is mixed into epoxy resin and glass fiber cloth is immersed in epoxy resin, EP / B / ADP8 / MPBA 7 It means that 8% by mass of aluminum diethylphosphinate and 7% by mass of melamine compound are mixed into epoxy resin and glass fiber cloth is immersed in epoxy resin, EP / B / ADP 10 / MPBA 5 It means that 10% by mass of aluminum diethylphosphinate and 5% by mass of melamine compound are mixed into epoxy resin and glass fiber cloth is immersed in the epoxy resin.

[0078] like Figure 5 As shown, the epoxy resin only impregnated with glass fiber cloth: the LOI value is 22.3%, and the vertical burning level is V-2. This shows that it has the worst flame retardant performance, a low limiting oxygen index and cannot pass the highest level UL-94 burning test. Adding 15% melamine compound: the LOI value is 26.1%, and the vertical burning level is V-1. Compared with pure epoxy resin, the flame retardant performance is improved, the LOI is increased, but it still does not reach the best burning level (V-0). Adding 15% aluminum diethylphosphinate: the LOI value is 35.4%, and the vertical burning level is V-0; this sample shows excellent flame retardant performance, the LOI is significantly improved, and it reaches the highest level (V-0) of UL-94, which means that it failed to continue burning in the burning test. Adding 8% aluminum diethylphosphinate and 7% melamine compounds: LOI value is 33.9%, vertical combustion grade is V-0; this combination also has very good flame retardant performance, although LOI is slightly lower than that of adding 15% aluminum diethylphosphinate, it still reaches the highest combustion grade of UL-94. Adding 10% aluminum diethylphosphinate and 5% melamine compounds: LOI value is 36.1%, vertical combustion grade is V-0; this ratio has the best flame retardant effect, the highest LOI, and the vertical combustion performance reaches V-0.

[0079] In summary, the dilution gas effect and endothermic effect of melamine compounds, combined with the free radical capture and carbonization layer generation of aluminum diethylphosphinate in the gas phase and condensed phase, form a synergistic flame retardant effect. Combined with the physical barrier effect of glass fiber cloth, the material exhibits an excellent flame retardant grade (V-0) and a high limiting oxygen index (LOI) in the vertical burning test (UL-94), and also has excellent anti-dripping performance.

[0080] Figure 6 The vertical combustion (UL-94) diagram of epoxy resin-glass fiber cloth-melamine compound-diethylphosphinate aluminum blended epoxy resin prepared by the present invention is shown in FIG. EP / B represents pure epoxy resin impregnated with glass fiber cloth, and EP / B / MPBA represents 15 It means that 15% of melamine compound is mixed into epoxy resin and glass fiber cloth is immersed in epoxy resin, EP / B / ADP15 It means that 15% of aluminum diethylphosphinate is mixed into epoxy resin and glass fiber cloth is immersed in epoxy resin, EP / B / ADP 8 / MPBA 7 It means that 8% by mass of aluminum diethylphosphinate and 7% by mass of melamine compound are mixed into epoxy resin and glass fiber cloth is immersed in epoxy resin, EP / B / ADP 10 / MPBA 5 It means that 10% by mass of aluminum diethylphosphinate and 5% by mass of melamine compound are mixed into epoxy resin and glass fiber cloth is immersed in the epoxy resin.

[0081] like Figure 6 As shown in the figure, EP / B itself has a low LOI value, indicating that it is easy to burn in an oxygen environment, and because no flame retardant is added, it lacks effective suppression of heat release and flame propagation during combustion. During the combustion process, molten drips may be generated and promote flame spread, resulting in a UL 94 rating of only V-2, which indicates that the system has not undergone any flame retardant modification and is prone to continuous combustion. Although glass fiber cloth itself has good flame retardant properties, in some extreme environments, it is still necessary to further enhance its flame retardant effect or improve its mechanical properties by other means. The synergistic effect of ADP and MPBA exerts the best flame retardant effect. ADP provides gas phase dilution and solid carbon layer protection, while MPBA enhances heat insulation and oxygen isolation through the expanded carbon layer. When the two are combined, the LOI is significantly improved and reaches the V-0 level. Combining the physical isolation of the expanded carbon layer and the chemical dilution mechanism of the gas phase flame retardant, it has excellent flame retardancy and stability. This combination has important practical application potential in the development of flame retardant materials.

[0082] Figure 7 The tensile test diagram of the epoxy resin-glass fiber cloth-melamine compound-diethylphosphinate aluminum blended epoxy resin prepared by the present invention is shown in FIG. EP / B represents pure epoxy resin impregnated with glass fiber cloth, and EP / B / MPBA represents 15 It means that 15% of melamine compound is mixed into epoxy resin and glass fiber cloth is immersed in epoxy resin, EP / B / ADP 15 It means that 15% of aluminum diethylphosphinate is mixed into epoxy resin and glass fiber cloth is immersed in epoxy resin, EP / B / ADP 8 / MPBA 7 It means that 8% by mass of aluminum diethylphosphinate and 7% by mass of melamine compound are mixed into epoxy resin and glass fiber cloth is immersed in epoxy resin, EP / B / ADP 10 / MPBA 5It means that 10% by mass of aluminum diethylphosphinate and 5% by mass of melamine compound are mixed into epoxy resin and glass fiber cloth is immersed in the epoxy resin.

[0083] like Figure 7 As shown, the tensile test is used to evaluate the mechanical properties of epoxy resin, and it is found that the strength does not change monotonically, but it has a clear maximum value under a certain amount of glass fiber cloth, aluminum diethylphosphinate and melamine compound component composite material. It can be seen that the tensile strength and strain of pure epoxy resin with glass fiber cloth are 53.2MPa and 1.5%, respectively. When 15% of the newly synthesized melamine compound is added to the epoxy resin and the glass fiber cloth is immersed in the epoxy resin, the tensile strength and strain of the composite material / EP of the melamine compound component are increased to 31.2MPa and 1.3%, respectively. After 15% of aluminum diethylphosphinate is added to the epoxy resin and the glass fiber cloth is immersed in the epoxy resin, a tensile strength of 38.7MPa and a strain of 1.1% are presented. After 8% aluminum diethylphosphinate and 7% melamine compound are added to the epoxy resin and the glass fiber cloth is immersed in the epoxy resin, a tensile strength of 30.7MPa and a strain of 1.7% are presented. After 10% of aluminum diethylphosphinate and 5% of melamine compound were added to epoxy resin and the glass fiber cloth was immersed in the epoxy resin, a tensile strength of 43 MPa and a strain of 1.8% were shown, and both the tensile strength and the strain were significantly enhanced.

[0084] In summary, the introduction of glass fiber cloth provides a role in strengthening the matrix and improving the mechanical properties of epoxy resin. The synergistic effect of aluminum diethylphosphinate and melamine compounds produces a performance optimization effect. When these two additives are combined in a reasonable proportion, the stable structure of aluminum diethylphosphinate and the flame retardant properties of melamine compounds complement each other, so that the composite material is not only improved in strength, but also improved in toughness and deformation resistance. Therefore, the reason for the performance improvement is that the reinforcing effect of glass fiber cloth and the synergistic effect of aluminum diethylphosphinate and melamine compounds jointly optimize the mechanical properties of the composite material.

[0085] Figure 8 The bending test diagram of the epoxy resin-glass fiber cloth-melamine compound-diethylphosphinate aluminum blended epoxy resin prepared by the present invention is shown in FIG. EP / B represents pure epoxy resin impregnated with glass fiber cloth, and EP / B / MPBA represents 15 It means that 15% of melamine compound is mixed into epoxy resin and glass fiber cloth is immersed in epoxy resin, EP / B / ADP 15 It means that 15% of aluminum diethylphosphinate is mixed into epoxy resin and glass fiber cloth is immersed in epoxy resin, EP / B / ADP 8 / MPBA 7 It means that 8% by mass of aluminum diethylphosphinate and 7% by mass of melamine compound are mixed into epoxy resin and glass fiber cloth is immersed in epoxy resin, EP / B / ADP 10 / MPBA 5 It means that 10% by mass of aluminum diethylphosphinate and 5% by mass of melamine compound are mixed into epoxy resin and glass fiber cloth is immersed in the epoxy resin.

[0086] like Figure 8 As shown, the tensile test is used to evaluate the mechanical properties of epoxy resin, and it is found that the strength does not change monotonically, but has a clear maximum value under a certain amount of glass fiber cloth, aluminum diethylphosphinate and melamine compound component composite material. It can be seen that the stress and strain of pure epoxy resin with glass fiber cloth are 75MPa and 5.0%, respectively. When 15% of the newly synthesized melamine compound is added to the epoxy resin and the glass fiber cloth is immersed in the epoxy resin, the stress and strain of the composite material / EP of the melamine compound component are increased to 63.1MPa and 2.7%, respectively. After 15% of aluminum diethylphosphinate is added to the epoxy resin and the glass fiber cloth is immersed in the epoxy resin, a stress of 52MPa and a strain of 2.5% are presented. After 8% aluminum diethylphosphinate and 7% melamine compound are added to the epoxy resin and the glass fiber cloth is immersed in the epoxy resin, a stress of 40MPa and a strain of 2.9% are presented. After 10% aluminum diethylphosphinate and 5% melamine compound were added to epoxy resin and the glass fiber cloth was immersed in the epoxy resin, a stress of 65 MPa and a strain of 2.9% were presented, and both the tensile strength and strain were significantly enhanced.

[0087] In summary, it can be seen that due to the high tensile strength and good deformation resistance of glass fiber, the externally applied load can be evenly distributed throughout the matrix, thereby significantly improving the overall mechanical strength and deformation resistance of the composite material. The addition of aluminum diethylphosphinate and melamine compounds not only has a significant effect on the mechanical properties, but also improves the thermal stability and flame retardant properties of the composite material. As a phosphorus-containing flame retardant, aluminum diethylphosphinate can react chemically with the epoxy resin matrix to form a stable phosphate structure, thereby increasing the crosslinking density and thermal decomposition temperature of the composite material. The strengthening effect of this crosslinked network structure helps to improve the strength and rigidity of the material.

Claims

1. A method for preparing a highly flame-retardant and high-toughness epoxy resin-glass fiber cloth-melamine compound-diethylphosphinate aluminum blended epoxy resin, characterized in that The preparation method is carried out according to the following steps: Step S1: Adding melamine compound and / or aluminum diethylphosphinate to epoxy resin, stirring magnetically at a temperature of 90 to 110° C. under ultrasonic conditions until the mixture is uniform, adding curing agent, and continuing magnetic stirring until the mixture is uniform, to obtain an epoxy resin mixed solution; the addition amounts of aluminum diethylphosphinate and melamine compound are 8% and 7%, 9% and 6%, 10% and 5%, 15% and 0%, or 0% and 15% of the mass of the epoxy resin, respectively; Step S2: Pour the epoxy resin mixed solution obtained in step S1 evenly into the mold, and then immerse the cut glass fiber cloth in the epoxy resin mixed solution, and ensure that the epoxy resin mixed solution is evenly filled in the gaps between the fibers of the glass fiber cloth; Step S3: The film mold in step S2 is placed in a vacuum oven for temperature gradient curing. After complete curing, a highly flame-retardant and high-toughness epoxy resin-glass fiber cloth-melamine compound-diethylaluminum phosphinate blended epoxy resin is obtained.

2. The method for preparing a highly flame-retardant and high-toughness epoxy resin-glass fiber cloth-melamine compound-diethylphosphinate aluminum blended epoxy resin according to claim 1, characterized in that The melamine compound described in step S1 is prepared according to the following steps: Under the condition of condensation and reflux, melamine is added into deionized water, an oil bath is heated to 80-100° C., and after stirring until the melamine is fully dissolved, a phytic acid solution at 60-70° C. is uniformly added, and then condensation reflux is stirred at 80-100° C. for 1 h to 2 h to obtain a light silver precipitate; a boric acid solution at 60-70° C. is continuously added uniformly, and condensation reflux is continuously stirred at 80-100° C. for 1 h to 2 h to obtain a flocculent precipitate; the flocculent precipitate is filtered, and then washed with deionized water three times and dried to obtain a melamine compound.

3. The method for preparing a highly flame-retardant and high-toughness epoxy resin-glass fiber cloth-melamine compound-diethylphosphinate aluminum blended epoxy resin according to claim 2, characterized in that The product is first washed in deionized water at 50-60° C., and then placed in a vacuum oven for drying. The above operation is then repeated twice, and finally dried at 70-80° C. overnight to obtain a melamine compound.

4. The method for preparing a highly flame-retardant and high-toughness epoxy resin-glass fiber cloth-melamine compound-diethylphosphinate aluminum blended epoxy resin according to claim 2, characterized in that The ratio of the mass of melamine to the volume of deionized water is (9.2-9.6) g: (300-350) mL; the ratio of the mass of phytic acid in the phytic acid solution to the volume of deionized water is (11.6-12.1) g: (30-35) mL; and the ratio of the mass of boric acid in the boric acid solution to the volume of deionized water is (1.45-1.65) g: (15-20) mL.

5. The method for preparing a highly flame-retardant and high-toughness epoxy resin-glass fiber cloth-melamine compound-diethylphosphinate aluminum blended epoxy resin according to claim 1, characterized in that The ultrasonic time in step S1 is 10 to 20 minutes.

6. The method for preparing a highly flame-retardant and high-toughness epoxy resin-glass fiber cloth-melamine compound-diethylphosphinate aluminum blended epoxy resin according to claim 1, characterized in that The magnetic stirring time in step S1 is 2 to 4 hours, and the magnetic stirring time is continued for 45 to 60 minutes.

7. The method for preparing a highly flame-retardant and high-toughness epoxy resin-glass fiber cloth-melamine compound-diethylphosphinate aluminum blended epoxy resin according to claim 1, characterized in that The curing agent in step S1 is diaminodiphenylmethane, and the added amount of diaminodiphenylmethane is 0.25-0.26% of the mass of the epoxy resin.

8. The method for preparing a highly flame-retardant and high-toughness epoxy resin-glass fiber cloth-melamine compound-diethylphosphinate aluminum blended epoxy resin according to claim 1, characterized in that The temperature gradient curing described in step S3 is: first curing at 80-100° C. for 1-2 hours, then curing at 100-120° C. for 1-2 hours, and then curing at 120-140° C. for 1-2 hours.

9. The method for preparing a highly flame-retardant and high-toughness epoxy resin-glass fiber cloth-melamine compound-diethylphosphinate aluminum blended epoxy resin according to claim 1, characterized in that The added amounts of the aluminum diethylphosphinate and the melamine compound are 8% and 7% or 10% and 5% of the mass of the epoxy resin respectively.

10. Use of a highly flame-retardant and highly tough epoxy resin-glass fiber cloth-melamine compound-diethylphosphinate aluminum blended epoxy resin prepared by the method according to any one of claims 1 to 9, characterized in that The application of the highly flame-retardant and high-toughness epoxy resin-glass fiber cloth-melamine compound-diethylphosphinate aluminum blended epoxy resin in environmentally friendly halogen-free flame-retardant materials.